Organic matter in carbonaceous chondrite lithologies of Almahata Sitta: Incorporation of previously unsampled carbonaceous chondrite lithologies into ureilitic regolith. (19th July 2021) - Kebukawa, Yoko; Zolensky, Michael. E.; Goodrich, Cyrena A.; Ito, Motoo; Ogawa, Nanako O.; Takano, Yoshinori; Ohkouchi, Naohiko; Kiryu, Kento; Igisu, Motoko; Shibuya, Takazo; Marcus, Matthew A.; Ohigashi, Takuji; et al.
Abstract: The Almahata Sitta (AhS) meteorite is a unique polymict ureilite. Recently, carbonaceous chondritic lithologies were identified in AhS. Organic matter (OM) is ubiquitously found in primitive carbonaceous chondrites. The molecular and isotopic characteristics of this OM reflect its origin and parent body processes, and are particularly sensitive to heating. The C1 lithologies AhS 671 and AhS 91A were investigated, focusing mainly on the OM. We found that the OM in these lithologies is unique and contains primitive isotopic signatures, but experienced slight heating possibly by short‐term heating event(s). These characteristics support the idea that one or more carbonaceous chondritic bodies were incorporated into the ureilitic parent body. The uniqueness of the OM in the AhS samples implies that there were large variations in primitive carbonaceous chondritic materials in the solar system other than known primitive carbonaceous chondrite groups such as CI, CM, and CR chondrites.